Volkameria inermis: An overview of its chemical constituents and pharmacological properties, notably the amelioration of motor tics - Eric Wei Chiang Chan; Siu Kuin Wong; Hung Tuck Chan (Shahrekord University of Medical Sciences, 2023)
This overview on Volkameria inermis (Lamiaceae) is the first in updating information on the chemical constituents and pharmacological properties of the species, notably on its unique ability in ameliorating motor tics. The information was procured from Google, Google Scholar, PubMed, PubMed Central, Science Direct, J-Stage, and PubChem. Previously named Clerodendrum inerme (Verbenaceae), V. inermis is a scrambling or scandent coastal shrub in the tropics and sub-tropics. From different parts of the plant, compounds such as flavonoids, diterpenes/diterpenoids, sterols, triterpenes/triterpenoids, iridoid glycosides, phenolic glycosides, phenylethanoid glycosides (PEGs), phenylpropanoid glycosides (PPGs), chalcones, and sesquiterpenes have been reported. Major pharmacological properties of V. inermis include anti-cancer, anti-inflammatory, antioxidant, hepatoprotective, analgesic, and antibacterial activities. Other properties include anti-tyrosinase, antifungal, neuroprotective, hypotensive, hypoglycemic, amyloid-β aggregation, wound healing, antipyretic, and larvicidal activities. A unique pharmacological property of V. inermis leaf extract, discovered by scientists from Taiwan, is the amelioration of motor tic disorders, a spectrum of Tourette syndrome. This property included a case report, three in vivo studies, and one patent. Areas of further research of V. inermis are suggested.